Acceleration and secular trend in a survey ot the Olomouc children and youth - Riegerova, Jarmila (Polskie Towarzystwo Antropologiczne, 1995)
ACCELERATION AND SECULAR TREND IN A SURVEY OF OLOMOUC CHILDREN AND YOUTH. On the basis of the graphs and standardization indexes we document the changes of basic anthropometric characteristics in a period of 20 to 32 years.